One-pot three-component kabachnik-fields synthesis of alpha-aminophosphonates using H-beta zeolite catalyst - Tillu, V. H.; Dumbre, Deepa K.; Wakharkar, R. D.; Choudhary, Vasant R. (Tetrahedron Letters, 2011)
One-pot three-component Kabachnik-Fields synthesis of alpha-aminophosphonates with high yields from the reaction between carbonyl compound, primary amine, and substituted phosphite can be carried out in a short period, using H-beta zeolite as a reusable catalyst. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: Carbonyl compound; H-beta zeolite; Primary amine; Substituted phosphite